Reflecting on practices: new directions for spatial theories - Landau, Friederike; Carlsson, Hanna; Lagendijk, Arnoud (Agenda Publishing Limited, 2024)
This collection of essays aims to better understand what researchers do when they practice research. The team of contributors – which includes human geographers, urban planners and environmental scientists – expose various epistemological, ontological and methodological challenges to pin down what practices "are". The essays showcase how practice theory can help spatial scientists generate new and future-oriented insights on debates such as mobility, relationality, and forms of critical spatial practice. In this way, the book reinforces a specifically geographic and spatial account that is needed for the development of practice theory while also shining new light on current debates within practice theory on power, politics and space. The book positions practices as the point of departure to study and conceptualize socio-spatial life